Case Report: Spontaneous recanalization of left anterior descending artery occlusive lesion with OCT-guided drug-coated balloon therapy - Yang, Bangguo; Yeh, Mengqi; Bai, Jie (Frontiers in Cardiovascular Medicine, 2024)
In instances where a patient with acute myocardial infarction (AMI) did not undergo immediate reperfusion therapy during the acute phase, there was a risk of the occlusion progressing to chronic and the chances of spontaneous recanalization decreasing. This case report detailed the experience of a 37-year-old male patient who, 45 days post-AMI, still had a blocked left anterior descending (LAD) artery due to the patient's refusal for intervention. Two years later, a follow-up coronary angiography showed spontaneous recanalization of the LAD artery, with haziness in the middle segment. Optical coherence tomography (OCT) revealed a honeycomb-like structure in the mid-LAD with a minimum area of 0.55 mm2. The lesion was effectively treated with a drug-coated balloon, resulting in an excellent outcome.